A DIGITAL INTERACTIVE MODULE-BASED ON PROBLEM LEARNING IN ENVIRONMENTAL POLLUTION - Riza Ulhaq; Ilham Juliwardi (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2023)
The background of this research is the lack of innovative digital technology-based learning media. There are not many digital interactive modules that have been developed to support learning. The limited availability of digital interactive modules can limit the use of technology in learning and hinder the achievement of learning goals in the era of Industrial Revolution 4.0. For this reason, it is necessary to develop digital-based interactive modules that provide opportunities for students to discover for themselves the concepts they are studying. Learners become more active and independently build knowledge. Research and development used the Borg and Gall model, which consists of product development, product validation, design revision, testing, and product revision. The research instrument consisted of a module validation questionnaire (content and media) and a response questionnaire. Module validation involves lectures at Teuku Umar University who are experts in their fields as content and media expert. The experts validation results obtained a combined score of 87.5%, indicating that the module can be used without repair. The product field test was carried out in the odd semester of the 2023–2024 academic year with 60 students at SMP Negeri 1 Aceh Barat. Field test results showed that 91% of students gave positive responses to the module. The development of digital-based interactive problem-based learning modules meets the requirements, can be used to facilitate active, creative learning, leads to the development of students' skills independently, and is relevant to technological developments.